PERKEMBANGAN PENDIDIKAN MAN 2 MODEL PEKANBARU (2010-2015) - Fatimah '; Isjoni '; Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: MAN 2 Model was established in 1960 under the name PGAN Pekanbaru. Education facilities and infrastructure MAN 2 Model Pekanbaru year 2010-2015 has increased, facilities and infrastructure is complete from laboratory, language laboratory, biology laboratory, chemistry, physics and religious facilities such as mosques, and sports facilities. Learners in 2010-2015 continue to experience improvement, this is due to the high interest of prospective students who want to continue their education to MAN 2 Model Pekanbaru. The development of teachers in 2010 -2015 also increased. Factors driving the development of education MAN 2 Model Pekanbaru such as, educators have a background of S1 qualifications in accordance with the subjects, madrasah has a clear division of tasks, facilities and educational infrastructure in the madrasah adequate, while the factors hampering the development of MAN 2 Model Pekanbaru is caused by, among others, the students' learning motivation is still low, there is still a low level of teacher discipline.Keywords: Development, Education, MAN 2 Model Pekanbaru